Clinical Practice Guidelines for Intracranial Tumours Treatment - Danny Barrueta Reyes; Juan Guillermo Trigo Naranjo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Intracranial Tumours Treatment. We review the physiopathology, diagnosis (stressing screening studies) and treatment. It includes assessment guidelines focused on the most important aspects to be accomplished.